Syari'ah - Fiqih - Hukum Islam : Studi tentang Konstruksi Pemikiran Kontemporer - Syafaul Mudawam (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
Islamic terminology, according to contemporary Islamic studies, has led to serious confusion, if Sharia terminology studied in the narrow sense, and the proportion of study Law. Sharia is built in the classical period, even up to the contemporary period substantively unchanged, ie as the basis for determining the rules of Islamic legal norms from authentic sources (al-Quran and as-Sunnah). Norma managed Shariah law has symmetry relations with other Islamic values (ethics and theology), it's all equally reduced from the original sour ces of the Qur'an and the Sunnah, then externalized in action for religious entities. In this case, the Shariah, Fiqh and Islamic Law is located on the same ordinate point and not on the same precision, because each has been studied and developed by different professions and disciplines, them were the Ulama, Fuqaha, Qadi and Legal Expert .